ANALISIS FAKTOR YANG MEMPENGARUHI PENGOLAHAN LIMBAH KAKAO MENJADI PAKAN TERNAK DI PT BERAU COCOA, KALIMANTAN TIMUR - Anthonius Dhinar Hasto Wisnugroho; Hamim Rachman (Jurnal Inkofar, 2021)
Waste is the residual product from an industrial process and the household, useless, no economic value and is a serious problem in the industrial era 4.0, where regulations on environmentally friendly industrialization are an important issue. Primary industries such as sugar cane, oil palm, cocoa produce a lot of wastes during the pre-harvest period such as leaves and three litters, and in the post-harvest period such as pulp, fruit skins, and fruit pulp. PT Berau Cocoa processes cocoa skin waste into animal feed which is applied to cattle in Binungan. This research uses a descriptive research method and how to teach data by distributing 50 questionnaires to cocoa farmers. The results of data analysis show the fact that most cocoa farmers are male of 38 peoples (76%), high school education level of 33 peoples (82%), joined along 4-6 years as 45 peoples (90 %), all respondents are married, and own private land. Supporting factors that influence the processing of cocoa waste into animal feed can be seen from the average value of each factor, method factor (0.596), material factor (0.512), human factor (0.416), and money factors (0.404), and the lowest average is the engine factor (0.312).